Boris Boris Piotrowski (1908-1990) (ՀՀ ԳԱԱ)
B.B. Piotrovski was a prominent Soviet archaeologist whose studies were devoted to the ancient Near Eastern and other archaeological cultures on the territory of the USSR. Among his scholarly interests was also the archaeology and history of the Armenian Highland (Urartu). B.Piotrovski was born in Saint-Petersburg in February 14, 1908 to the family of teachers. In 1925 he entered the department of linguistics and material culture of the Leningrad state university where he studied ancient Near Eastern and Egyptian archaeology. Among his teachers were well known Soviet archaeologists - V.Struve, N.Flitner, A.Miller, etc.
Keywords: Archaeology; Biography